2015
DOI: 10.3164/jcbn.14-71
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of nitrergic nerve in canine gingival reactive hyperemia

Abstract: Reactive hyperemia reflects a compensatory vasodilation response of the local vasculature in ischemic tissue. The purpose of this study is to clarify the mechanism of regulation of this response in gingival circulation by using pharmacological analysis of reactive hyperemia and histochemical analysis of gingival tissue. Application of pressure to the gingiva was used to create temporary ischemia, and gingival blood flow was measured after pressure release. Reactive hyperemia increased in proportion to the dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…These results indicated that NO played a major role in RH as a non-cholinergic, non-adrenergic, and non-histaminergic regulatory agent. ( 2 , 3 ) Previous findings obtained in dog gingiva were consistent with our results on the suppression of rat gingival RH. Toda et al ( 20 ) showed that the nitrergic nerve acted as a vasodilator.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results indicated that NO played a major role in RH as a non-cholinergic, non-adrenergic, and non-histaminergic regulatory agent. ( 2 , 3 ) Previous findings obtained in dog gingiva were consistent with our results on the suppression of rat gingival RH. Toda et al ( 20 ) showed that the nitrergic nerve acted as a vasodilator.…”
Section: Discussionsupporting
confidence: 93%
“…We previously demonstrated using NO electrodes that NO directly played a role in dog gingival RH; the NO current was slowly elevated in dog gingival tissues during ischemia. ( 2 ) RH subsequently occurred in parallel with a marked elevation in the NO current. RH was not affected by cholinergic blocking agents, adrenergic blocking agents, or antihistaminic agents, and was markedly suppressed by l -NAME.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There are several animal studies demonstrating that the endothelial or neuronal release of NO has a fundamental role in both the maintenance and the regulation of gingival blood flow (GBF) in reactive hyperaemia as well as in the pathophysiology of periodontitis . Endothelial and inducible nitric oxide synthases were found in human gingival tissue, but direct evidence of the contribution of NO to the regulation of human GBF has not been demonstrated yet.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 It is observed in several tissues such as the lymphatics, 11 the intestines, 12 the skeletal muscles, [13][14][15] the brain, 16,17 the kidneys 18,19 and the mesentery. 20 There are several animal studies demonstrating that the endothelial or neuronal release of NO has a fundamental role in both the maintenance and the regulation of gingival blood flow (GBF) [21][22][23][24] in reactive hyperaemia 25,26 as well as in the pathophysiology of periodontitis. [27][28][29] Endothelial and inducible nitric oxide synthases were found in human gingival tissue, 27,[29][30][31] but direct evidence of the contribution of NO to the regulation of human GBF has not been demonstrated yet.…”
Section: Introductionmentioning
confidence: 99%